Unraveling the Complexity of Imported Malaria Infections by Amplicon Deep Sequencing - He, Xi; Zhong, Daibin; Zou, Chunyan; Pi, Liang; Zhao, Luyi; Qin, Yucheng; Pan, Maohua; Wang, Siqi; Zeng, Weiling; Xiang, Zheng; Chen, Xi; Wu, Yanrui; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Imported malaria and recurrent infections are becoming an emerging issue in many malaria non-endemic countries. This study aimed to determine the molecular patterns of the imported malaria infections and recurrence. Blood samples were collected from patients with imported malaria infections during 2016–2018 in Guangxi Zhuang Autonomous Region, China. Next-generation amplicon deep-sequencing approaches were used to assess parasite genetic diversity, multiplexity of infection, relapse, recrudescence, and antimalarial drug resistance. A total of 44 imported malaria cases were examined during the study, of which 35 (79.5%) had recurrent malaria infections within 1 year. The majority (91.4%) had one recurrent malaria episode, whereas two patients had two recurrences and one patient had three recurrences. A total of 19 recurrence patterns (the species responsible for primary and successive clinical episodes) were found in patients returning from malaria epidemic countries. Four parasite species were detected with a higher than usual proportion (46.2%) of non-falciparum infections or mixed-species infections. An increasing trend of recurrence infections and reduced drug treatment efficacy were observed among the cases of imported malaria. The high recurrence rate and complex patterns of imported malaria from Africa to non-endemic countries have the potential to initiate local transmission, thereby undermining efforts to eliminate locally acquired malaria. Our findings highlight the power of amplicon deep-sequencing applications in molecular epidemiological studies of the imported malaria recurrences.